Hubungan Efikasi Diri Dengan Tingkat Kecemasan Mahasiswa Tahun Pertama di Fakultas Kedokteran Universitas Lampung Tahun 2018 - Habibi Adhi Pratama Duarsa; Oktafany; Dian Isti Angraini (Medula, 2020)
Anxiety can be experienced by all students, especially students who have heavy college burden, such as students of medical education study programs. Excessive anxiety can hurt students because it can affect student learning outcomes. Self-efficacy is a belief in one's ability to achieve an expected outcome, self-efficacy is known to play an important role in anxiety. This study aims to determine the correlation between self-efficacy and the anxiety level of first year medical student in lampung university. This study uses a cross sectional approach. The sample in the study were 183 respondents and were asked to fill in two questionnaires, namely the General Self-Efficacy and Zung Self Anxiety Scale. Based on univariate analysis found low self efficacy of 6.6%, moderate self efficacy of 77.6%, and high self efficacy of 15.8%. At the level of anxiety found not experiencing anxiety 23.5%, mild-moderate anxiety 71.0%, and severe anxiety 5.5%. Based on bivariate analysis with Gamma test, there was a significant correlation between self-efficacy and anxiety with a value (p = 0,0001), with the degree of closenses of a strong negative correlation ( = -0.657). The conclusion if self-efficacy higher then anxiety level gets lower, vice versa.